2022
DOI: 10.3389/fcimb.2022.998600
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis induced by Porphyromonas gingivalis drives impaired glucose metabolism in mice

Abstract: Periodontitis has been demonstrated to be bidirectionally associated with diabetes and has been recognized as a complication of diabetes. As a periodontal pathogen, Porphyromonas gingivalis is a possible pathogen linking periodontal disease and systemic diseases. It has also been found to be involved in the occurrence and development of diabetes. In this study, 6-week-old male C57BL/6 mice were orally administered the P. gingivalis strain ATCC381 for 22 weeks. Histological analysis of the gingival tissue and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The level of insulin resistance was significantly elevated. Furthermore, Luan et al utilized P. gingivalis to establish an animal model [ 29 ]. They revealed that the levels of TNF-α and IL-6 were increased and the expression of PPARa, Irs1, and sitr1 was decreased, which suggested that glucose metabolism was dysregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The level of insulin resistance was significantly elevated. Furthermore, Luan et al utilized P. gingivalis to establish an animal model [ 29 ]. They revealed that the levels of TNF-α and IL-6 were increased and the expression of PPARa, Irs1, and sitr1 was decreased, which suggested that glucose metabolism was dysregulated.…”
Section: Discussionmentioning
confidence: 99%
“…21 It is believed that periodontitis and diabetes are related in a bidirectional manner. 22,23 Treatment modalities for periodontitis with T2DM are being explored. It is realized that effectively promoting alveolar bone regeneration in the inflammation resolution stage may provide a new perspective on periodontitis with T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is an inflammatory disease that leads to inflammatory bone loss around teeth 21 . It is believed that periodontitis and diabetes are related in a bidirectional manner 22,23 . Treatment modalities for periodontitis with T2DM are being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Seyama et al, 2020 study found that outer membrane vesicles released by P. gingivalis attenuated Akt/glycogen synthase kinase-3b (GSK-3b) signaling in hepatic HepG2 cells, inducing insulin resistance and allowing insulin-induced reduction in hepatic glycogen synthesis, thereby maintaining high blood glucose levels (Seyama et al, 2020). Bhat et al, 2014 demonstrated that P.g-LPS stimulates insulin secretion from the pancreatic b-cell lineage MIN cells.P.g-LPS may be important in the development of b-cell compensation and insulin resistance in patients with periodontitis in prediabetes (Bhat et al, 2014).Tian, J et al an animal study showed that P. gingivalis periodontal infection significantly upregulated plasma branched-chain amino acid levels and exacerbated The plasma branched-chain amino acid biosynthetic pathway may provide a potential target for the link between periodontitis and T2DM (Kang et al, 2022).…”
Section: Diabetesmentioning
confidence: 99%
“…P.g -LPS may be important in the development of b-cell compensation and insulin resistance in patients with periodontitis in prediabetes ( Bhat et al., 2014 ).Tian, J et al. an animal study showed that P. gingivalis periodontal infection significantly upregulated plasma branched-chain amino acid levels and exacerbated The plasma branched-chain amino acid biosynthetic pathway may provide a potential target for the link between periodontitis and T2DM ( Kang et al., 2022 ).…”
Section: Association Of P Gingivalis With Systemic...mentioning
confidence: 99%